Influence of small amounts of Si and Cr on the high temperature oxidation behavior of novel cobalt base superalloys - Liang, Zhida; Göken, Mathias; Lorenz, Uwe; Neumeier, Steffen; Oehring, Michael; Pyczak, Florian; Stark, Andreas; Wang, Li (Corrosion Science, 2021)
The effect of small amounts of Si and Cr on the high temperature oxidation of alloys based on Co-9Al-9W was investigated at 900 °C. The results show that the effect of Si additions on oxidation resistance was more pronounced than for Cr additions. An addition of 4 at.% Cr was insufficient to produce a protective layer, while 2 at.% Si led to the formation of a dense, continuous Al2O3 scale. The thermodynamics and kinetics for Al2O3 layer formation were analyzed by combining CALPHAD and Wagnerʼs theory.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Co-based superalloys; Oxidation; Synchrotron radiation; Thermodynamics and kinetics